IDENTIFIKASI DAN KARAKTERISASI MORFOLOGI TUMBUHAN MAKROFITA DI DANAU TOBA, KECAMATAN PALIPI, KABUPATEN SAMOSIR, PROVINSI SUMATERA UTARA - Helda Simbolon; Nery Sofiyanti (Universitas Lambung Mangkurat, 2026)
Macrophytic plants are plants that spend most of their life cycle in water which plays an important role in aquatic ecosystems. Macrophytic plants are pivotal for fish habitat in Lake Toba, Palipi District, such as for shelter, forage and also a place to attach eggs. These plant groups are also important to maintain water quality. The purpose of this study is to provide data on macrophyte plant species and their morphological characteristics in Lake Toba, Palipi District, Samosir Regency, North Sumatra Province. Sampling was carried out using an exploration method. The morphological characters were observed and photographed. The data obtained is then explained in the form of figures and tables, scoring is carried before being analyzed using NTSys pc 2.02 application to obtain the similarity coefficient and construct dendrogram. The results of this study were obtained from 9 types of macrophyte plants (Alternanthera sessilis, Phragmites karka, Ipomoea aquatica, Salvinia minima, Limnocharis flava, Hydrilla verticillata, Vallisneria spiralis, Nymphaea rubra dan Eichorrnia crassipes). The dendrogram is divided into two groups I and II at a coefficient value of 0,28. The similarity coefficient ranges from 0,15 to 0,80. Dendrogram shows that each group is clustered based on growth type, stems and flowers.